Bioacoustic assessment of mangrove health: influence of habitat characteristics on bird richness - Abdul Rahim, Al-Kautsar Hidayanto; Puan, Chong Leong; Muhammad Adam Mah, Amera Natasha Mah; Zakaria, Mohamed; Jamaludin, Nurhaidah; Abdul Wahaf, Nurul Syafiqa (John Wiley and Sons Inc, 2025)
Mangroves play a vital role in coastal ecosystems, providing numerous ecosystem functions and services as well as supporting high levels of biodiversity. Using a bioacoustic approach, we assessed the influence of mangrove habitat variables on birds in four sites in Peninsular Malaysia. We set up 20 bioacoustic audio recorders across Telok Gong, Kapar Tambahan, Banjar Utara Forest Reserves, and Kuala Selangor Nature Park. The recorders operated for 30 min every hour over a period of 24 h for seven consecutive days. We assessed the habitat characteristics at each site by establishing one 20 m × 20 m quadrat at each of the recording points. Generalized linear mixed models indicated that the percentage of canopy cover, average tree height, forest age, number of saplings, forest size, and ground cover positively influenced bird richness. Our findings highlight the importance of maintaining these habitat features to support higher bird species richness in mangroves. This study demonstrated the possible use of bioacoustics to assess mangrove restoration recovery progress via birds as bioindicators. Abstract in Malay is available with online material.